(untitled) (Revista Iberoamericana de Bioética, 2019)
The characters within Luigi Pirandello’s novels portray real people whose topicality is undeniable. As such, the purpose of this article is to establish a comparison between the physician in Pirandello’s novels and the physician in Brazilian society nowadays, highlighting their professional conduct. The novels “The Doctor’s Duty”, “The Fly”, and “The Other Son” were analyzed in the light of the current Medical Ethics Code, conveying old problems that still remain these days. Reading Pirandello induces critical thinking of the medical practice, prompting the establishment of a physician-patient relationship based on exchanging experiences and sharing decisions.